Valor nutricional das silagens do híbrido de sorgo BRS610 em quatro estádios - Otaviano de Souza Pires Neto (2017)
The aim of this study was to evaluate the voluntary intake, apparent digestibility, nitrogen balance, energetic partitioning, ruminal degradation kinetics (in situ) and fermentation of BRS 610 sorghum hybrid silages (in vitro) at four maturation stages. The intakes of dry matter (DM) and organic matter (OM) in g/kg of PV0.75/day showed a linear behavior with the advancement of the cutting age of the plants for ensiling. The apparent digestibility of DM and MO also showed increasing linear behavior. Ingested nitrogen (IN) and fecal nitrogen were not different among silages of different stages of silage, urinary nitrogen presented a linear reduction, while retained nitrogen (RN) and NR / NI ratio presented increasing linear behavior. The consumption of crude, digestible, metabolizable and liquid energy in kcal/kg of PV0.75/day showed an increasing linear behavior with the maturity of the plant. Energy losses in faeces and urine presented linear reduction. However, the energy losses in the form of methane (CH4) and caloric increment did not present differences. The CH4 productions were not different among the silages. In the determination of ruminal degradation parameters (in situ), as well as the potential and effective degradability in the rates of passage of 2, 5 and 8%/h, the plant silage at 100 days was superior to the others, with potential DM degradability values and BP of 86.16% and 84.17%, respectively. As with the effective degradation of NDF, plant silage at 100 days was higher than the others, with values of 27.09, 14.77 and 10.15% in the rates of passage of 2, 5 and 8%, respectively. The soluble fraction "a" of DM had the highest value presented by plant silage at 107 days, whereas that same fraction of PB had higher value by plant silage at 100 days of age, with values of 34.47 and 54.52%, respectively. The insoluble fraction "b" with degradation potential of DM and PB had the highest values observed in plant silages at 100 and 121 days, respectively, with values of 55.23 and 39.18%. However, plant silages at 107 and 114 days presented higher values of "b" fraction in the degradation of NDF, with values of 84.14 and 84.53%, respectively. When evaluating silages in vitro, plant silage in the (milky grain stage) (100 days) presented a higher volume of gases from non - fibrous carbohydrate fraction (VF1), with 40.2 mL / g DM. The gases produced from the fibrous fraction of the four silages were shown to be close, with values ranging from 68.0 to 71.0 mL / g of DM. The high coefficient of determination (R2), both above 0.96, show that the results fit well with the model used in the evaluation. In the evaluation of the effective degradability (ED) of the DM, the silage of the plant at 100 days was superior to the others, when evaluated in the rates of passage of 2, 5 and 8% / h, with values of 40,18, 37,23 and 34.36% of DM, respectively. The sorghum hybrid BRS 610 must be cut for silage from 107 days (Grain pasty), because it is of better nutritional quality, when used by sheep.